Diagnostic utility of pharyngeal follicular structures in COVID-19: A large-scale cross-sectional study - Takahashi, Hidenori; Morikawa, Miwa; Satake, Yugo; Nagamatsu, Hiroki; Hirose, Ryutaro; Yamada, Yuka; Toba, Naoya; Toyama-Kousaka, Mio; Ota, Shinichiro; Shinoda, Masahiro; Mineshita, Masamichi; Shinkai, Masaharu (International journal of infectious diseases, 2024)
•Pharyngeal follicles are potential early-stage COVID-19 diagnostic markers.•Follicular structures show 73.6% sensitivity for COVID-19 diagnosis.•Follicles are detectable regardless of vaccination status or virus strain.•Mixed follicle patterns may distinguish COVID-19 from influenza.•Cross-sectional study conducted on 1223 patients at Tokyo Shinagawa Hospital. Pharyngeal follicles similar to those seen in influenza have been observed in patients with coronavirus disease 2019 (COVID-19), suggesting their potential as early-stage diagnostic markers. In this study, we examined the diagnostic potential of pharyngeal follicles for COVID-19, particularly the Omicron variant and its subtypes, to obtain basic data for AI-based diagnostic imaging tools. A cross-sectional study was conducted from July 21, 2022, to March 31, 2023, at the Tokyo Shinagawa Hospital's fever clinic. Participants aged ≥15 years who underwent real-time polymerase chain reaction testing for COVID-19 and pharyngeal examinations were included. Demographic details, symptom onset, throat pain, and vaccination status were also recorded. Pharyngeal structures were categorized into four groups: follicles, buds, mixed, or absent. Of the 1223 participants, 829 (67.8%) tested positive for COVID-19. Among those who tested positive, 73.6% (95% CI: 70.6%-76.6%) had follicular structures, compared to 52.8% (95% CI: 47.9%-57.7%) of those who tested negative (P = 1.0 × 10−12). Overall, 818 participants exhibited follicular structures (439 with follicles, 281 with buds, and 98 with mixed structures), while 405 lacked any follicular structures. Regression analysis identified throat pain and follicular structures as significant COVID-19 predictors (95% confidence intervals: 2.49-4.85 and 1.43-2.59, respectively). Mixed follicles were identified as a potentially characteristic feature of COVID-19. Pharyngeal follicular structures demonstrated high sensitivity for early COVID-19 diagnosis. [Display omitted]